Relating functional changes during hand movement to clinical parameters in patients with multiple sclerosis in a multi-centre fMRI study. - Wegner, C; Filippi, M; Korteweg, T; Beckmann, C; Ciccarelli, O; De Stefano, N; Enzinger, C; Fazekas, F; Agosta, F; Gass, A; Hirsch, J; Johansen-Berg, H; et al. (2008)
We performed a prospective multi-centre study using functional magnetic resonance imaging (fMRI) to better characterize the relationships between clinical expression and brain function in patients with multiple sclerosis (MS) at eight European sites (56 MS patients and 60 age-matched, healthy controls). Patients showed greater task-related activation bilaterally in brain regions including the pre- and post-central, inferior and superior frontal, cingulate and superior temporal gyri and insula (P < 0.05, all statistics corrected for multiple comparisons). Both patients and healthy controls showed greater brain activation with increasing age in the ipsilateral pre-central and inferior frontal gyri (P < 0.05). Patients, but not controls, showed greater brain activation in the anterior cingulate gyrus and the bilateral ventral striatum (P < 0.05) with less hand dexterity. An interaction between functional activation changes in MS and age was found. This large fMRI study over a broadly selected MS patient population confirms that movement for patients demands significantly greater cognitive 'resource allocation' and suggests age-related differences in brain responses to the disease. These observations add to evidence that brain functional responses (including potentially adaptive brain plasticity) contribute to modulation of clinical expression of MS pathology and demonstrate the feasibility of a multi-site functional MRI study of MS.